Phases in development project, supervision, co-ordination. and project management and problems incurred and relate. Case Study: Wangsa Maju Entreprenuership (Hawthornden Estate)/ Siti Aminah Haji Abdul Aziz - Abdul Aziz, Siti Aminah (1985)
Wangsa Maju Newtownship the epitome of an ideal, well planned township, designed to promote the spirit of neighbourhood among residents. It is designed in accordance with the structure plan, equipped with socio-economic facilities and modern infrastructures. In line with the Government policies to provide better housing for the low income earners, the development pattern of Wangsa Maju Newtownship consists of 5 storeys walk-up flats surrounded by pedestrian malls free from traffic . Along the walkways are the green belts. The development of Wangsa Maju Newtownship is the first joint-venture project undertaken by Dewan Bandaraya Kuala Lumpur and Peremba Berhad. It is envisaged that this pioneer project will bring success not only to Dewan Bandaraya but to the implementation of the Malaysia "incorporated Concept" introduced by the Government.